2001
DOI: 10.1002/1438-9312(200106)103:6<341::aid-ejlt341>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Dietary trans α-linolenic acid does not inhibit Δ5- and Δ6-desaturation of linoleic acid in man

Abstract: Dietary trans monoenes have been associated with an increased risk of heart disease in some studies and this has caused much concern. Trans polyenes are also present in the diet, for example, trans α‐linolenic acid is formed during the deodorisation of α‐linolenic acid‐rich oils such as rapeseed oil. One would expect the intake of trans α‐linolenic acid to be on the increase since the consumption of rapeseed oil in the western diet is increasing. There are no data on trans α‐linolenic acid consumption and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
4
1
2
Order By: Relevance
“…This allowed each subject to serve as his own control. Contrary to the animal studies, this study failed to show consistent a inhibitory ef-fect of the trans α-linolenic acid isomers on the desaturation of linoleic acid [16].…”
Section: Trans α α-Linolenic Acid Isomers Plasma Fatty Acids and Thecontrasting
confidence: 99%
“…This allowed each subject to serve as his own control. Contrary to the animal studies, this study failed to show consistent a inhibitory ef-fect of the trans α-linolenic acid isomers on the desaturation of linoleic acid [16].…”
Section: Trans α α-Linolenic Acid Isomers Plasma Fatty Acids and Thecontrasting
confidence: 99%
“…Furthermore feeding to humans 18:3 isomers at 0.6% energy did not seem to affect the conversion of n-6 and n-3 fatty acids as no variation of 20:4n-6 and 22:6n-3 were observed under these conditions. The effects of these 18:3 isomers on the Δ6 desaturation of linoleic acid was further studied by Scrimgeour et al, (2001) using 3-oleyl, 1,2-(U-13 C)-labelled linoleic acid (15 mg twice daily for 10 days) in 7 healthy men from the TransLine study (Sebedio et al, 2000). The data indicated that a diet rich in trans α-linolenic acid at 0.6% energy does not inhibit the conversion of linoleic acid to dihomo-γ-linolenic and arachidonic acid in healthy middle-aged men consuming a diet rich in linoleic acid.…”
Section: E Human Studiesmentioning
confidence: 99%
“…O AGT C18:3n-3 também é capaz de inibir a ∆5-dessaturase e consequentemente impedir a formação de ácido araquidônico 40 . Portanto, os isômeros trans podem inibir a biossíntese de compostos importantes para o organismo humano.…”
Section: áCidos Graxos Transunclassified